Electrochemical studies of poly (3,4-ethylenedioxythiophene) PEDOT/VS2 nanocomposite as a cathode material for rechargeable lithium batteries - Murugan, A. Vadivel; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Electrochemistry Communications, 2005)
Here, we demonstrate the electrochemical characterization of a new type of layered poly (3,4-ethylenedioxythiophene) PEDOT/ VS2 nanocomposite. It has been prepared via flocculation of delaminated VS2 with subsequent in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. The interlayer spacing Of VS2 expands from 5.71 to 14.01 A and this interlayer separation is consistent with the existence of a monolayer of PEDOT in the VS2 framework. X-ray diffraction, XPS and TEM studies have been;shown the change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT/VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mAh/g) compared to that (80 mAh/g) for pristine VS2. (C) 2004 Published by Elsevier B.V.
Keywords: layered nanocomposite; lithium batteries; polythiophene; vanadium disulfide

Enhancement of double-layer capacitance behavior and its electrical conductivity in layered poly (3, 4-ethylenedioxythiophene)-based nanocomposites - Murugan, A. Vadivel; Viswanath, A. K.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Applied Physics Letters, 2005)
In this letter, we report on the enhanced double-layer capacitance of a layered poly (3, 4-ethylene dioxythiophene) PEDOT-MoO3 nanocomposite, which has been synthesized by a novel microwave irradiation method. The x-ray photoelectron spectroscopy analysis shows the changes in electron density and the shift in binding energy suggesting charge transfer from sulfur atoms upon PEDOT intercalation between MoO3 layers. The room-temperature conductivity for the PEDOT-MoO3 composite is found to be 1.82x10(-1) S cm(-1), which is four orders of magnitude higher than that of the pristine oxide (3.78x10(-5) S cm(-1)). The enhanced double-layer capacitance of the PEDOT-MoO3 nanocomposite (similar to 300 F g(-1)) compared to that (similar to 40 mF g(-1)) of pristine MoO3 is attributed to higher electronic conductivity, enhanced bidimensionality, and increase in surface area of the nanocomposite.

Entrapment of poly(3,4-ethylenedioxythiophene) between VS2 layers to form a new organic-inorganic intercalative nanocomposite - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Vijayamohanan, K. (Journal of Materials Chemistry, 2005)
Here we report the synthesis and characterization of a new class of nanocomposite by direct in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. Upon intercalation, the interlayer spacing of VS2 expands from 5.71 Angstrom to 14.01 Angstrom, followed by exfoliation and a restacking process facilitating expansion of the lattice in a direction perpendicular to the dichalcogenide layers. This change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The resulting nanocomposite is characterized by thermal analysis (TGA), X-ray diffraction, FTIR, SEM, TEM, and four-probe electrical conductivity measurements. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT-VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mA h g(-1)) compared to that (80 mA h g(-1)) for pristine VS2.

Electrochemical organization of monolayer protected gold nanoclusters on single-walled carbon nanotubes: significantly enhanced double layer capacitance - Mahima, Subhramanyam; Chaki, N. K.; Sharma, J.; Kakade, Bhalchandra A.; Pasricha, R.; Rao, A. M.; Vijayamohanan, K. (Journal of Nanoscience and Nanotechnology, 2006)
This paper reports a novel electrochemical route for anchoring monolayer protected gold nanoclusters (size 8 +/- 0.2 nm) on single-walled carbon nanotube bundles, resulting in the formation of hybrid materials. Monolayer protected gold nanoclusters prepared by modified Brust synthesis route were organized on SWNT bundles by cycling-the potential in dichloromethane between -1 to +1 V at a scan rate of 50 mV/s. Monolayer protected nanoclusters in electrolyte solutions possess ionic space charge around them (double layer charging), making them suitable for organization on nanotube bundles, by tuning the electrostatic interactions. More significantly, analysis of the double layer capacitance of these hybrid materials shows almost ten times increase in capacitance compared to that of bare SWNT bundles. We believe that these hybrid materials are potentially useful in nanoelectronics.
Keywords: double layer capacitance; double layer charging; hybrid materials; monolayer protected gold nanoclusters; single-walled carbon nanotubes

Exfoliation-induced nanoribbon formation of poly(3,4-ethylene dioxythiophene) PEDOT between MoS2 layers as cathode material for lithium batteries - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Power Sources, 2006)
A new type of layered nanocomposite synthesized by delaminated MoS2 nanosheets and poly(3,4-ethylenedioxythiophene) (PEDOT) are restacked to produce alternate polymer nanoribbons between layers Of MoS2 with an interlayer distance of similar to 1.38 nm. The unique properties of resulting nanocomposite are investigated by powder XRD, XPS, SEM, TEM, and four-probe conductivity measurements. The obtained nanocomposite can be used as a cathode material for a small power rechargeable lithium battery as demonstrated by the electrochemical insertion of lithium into the PEDOT/MoS2 nanocomposite. A significant enhancement in the discharge capacity (100 mAh g(-1)) is observed compared with that (40 mAh g(-1)) for MoS2. (c) 2005 Elsevier B.V All rights reserved.
Keywords: cathode material; lithium batteries; MoS2; organic-inorganic nanocomposite; PEDOT-nanoribbons

Effect of synthesis procedure on the structure and properties of palladium/polycarbonate nanocomposites - Valmikanathan, O. P.; Ostroverkhova, O.; Mulla, Imtiaz S.; Vijayamohanan, K.; Atre, S. V. (Polymer, 2008)
In this paper, we compare two procedures for the synthesis of palladium (Pd)/polycarbonate (PC) nanocomposites as well as their morphological, optical, thermal and electrical properties. Pd nanoclusters were produced by the reduction of palladium chloride using a variation of Brust's method. Discrete I'd nanoclusters of similar to 15 nm size were formed in the absence of PC in the reaction mixture (ex situ method) while agglomeration of Pd nanoclusters was noticed in the presence of PC in the reaction mixture (in situ method). Fourier transform infrared spectroscopy (FTIR) suggests nanoparticle-polymer interactions and polymer conformational changes in the in situ nanocomposite films. Even after having the same Pd content, the ex situ nanocomposites films were found to transmit more light than the in situ nanocomposites. The glass transition temperature (T-g), decreased by similar to 16 degrees C for both the ex situ and in situ samples. Thermogravimetric analysis (TGA) indicated that the presence of Pd nanoclusters significantly improved the thermal stability of the nanocomposites, as evidenced by the enhanced onset of degradation by similar to 20 degrees C and similar to 40 degrees C for the in situ and ex situ nanocomposites, respectively. The electrical conductivity measurement shows a dramatic difference between these nanocomposites with a significantly higher value for the in situ nanocomposite (resistivity = 2.1 X 10(5) Omega m) compared to the ex situ nanocomposite (resistivity = 7.2 x 10(13) Omega m). (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: in situ and ex situ syntheses; Morphology; Nanocomposites

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal